MUKtwelve protocol: a phase II randomised, controlled, open, parallel group, multicentre trial of selinexor, cyclophosphamide and prednisolone (SCP) versus cyclophosphamide and prednisolone (CP) in patients with relapsed or refractory multiple myeloma. Issue 10 (26th October 2022) - Kendall, Jessica; Hall, Andrew; Roberts, Sadie; Brown, Sarah; Boyd, Kevin; Auner, Holger W; Garg, Mamta; Kaiser, Martin
Abstract : Introduction: Multiple myeloma is a malignancy of plasma cells with around 6000 new cases per year in the UK. Cyclophosphamide plus prednisolone is considered a standard of care for disease and symptom control in the advanced relapsed or refractory myeloma setting within the UK NHS. The selective nuclear export inhibitor, selinexor, has been relatively well tolerated in previous clinical trials and offers promise when used in combination with a wide range of other anti-cancer treatments. Here, we investigate if the addition of selinexor can improve responses to cyclophosphamide plus prednisolone without adding prohibitive toxicity. Methods and analysis: MUKtwelve is a UK-based, randomised, controlled, open, parallel group, multicentre phase II trial designed to evaluate clinical efficacy of selinexor in combination with cyclophosphamide and prednisolone (SCP) in patients with relapsed or refractory multiple myeloma. A calibration arm will receive cyclophosphamide and prednisolone alone (CP). Participants who experience disease progression on the CP arm may, if eligible, receive SCP. The MUK twelve trial results will be the first to assess clinical efficacy of selinexor with low-dose CP in relapsed/refractory multiple myeloma. It is widely accepted that the relapsing-remitting nature of the disease is accompanied by cellular changes that often result in the requirement for novel agents and drug combinations to regain disease control. Patients also often experience cumulative toxicities throughout their treatments, limiting the treatment intensity that can be given at relapse. Thus, there is a need for novel effective combination therapies with acceptable toxicity profiles. Ethics and dissemination: Ethics approval is obtained. Results will be submitted for publication in a peer-reviewed journal. Trial registration number: ISRCTN15028850 .